2017
DOI: 10.1002/mrd.22921
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular Ca2+‐dependent full‐type hyperactivation in ejaculated boar spermatozoa preincubated with a cAMP analog

Abstract: Ejaculated boar spermatozoa exhibit two types of hyperactivation: full and non-full. Full-type hyperactivation is characterized by the asymmetrical bending of the entire middle piece-principal piece and a twisting/figure-eight-like trajectory, and can be induced by simple incubation with CaCl after preincubation with a cAMP analog (Sp-5,6-dichloro-1-β-D-ribofuranosyl-benzimidazole-3',5'-cyclic monophosphorothioate [cBiMPS]). Here, we compared the sperm flagellar motility after treatments with elevators of [Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
(114 reference statements)
0
22
0
Order By: Relevance
“…Suarez and her colleagues also confirmed that Ca 2+ can antisymmetrize flagellar bending by increasing the curvatures of the principal bend in detergent‐demembranated bull spermatozoa . Moreover, the treatment with the elevators of the intracellular Ca 2+ level can induce hyperactivation rapidly and highly in the uncapacitated spermatozoa in vitro . These results have established a current theory that the most important initiator of hyperactivation is a rapid increase of cytoplasmic Ca 2+ that is induced by the influx from extracellular space and recruitment from the internal store …”
Section: Regulatory Mechanisms For Flagellar Hyperactivationmentioning
confidence: 74%
See 4 more Smart Citations
“…Suarez and her colleagues also confirmed that Ca 2+ can antisymmetrize flagellar bending by increasing the curvatures of the principal bend in detergent‐demembranated bull spermatozoa . Moreover, the treatment with the elevators of the intracellular Ca 2+ level can induce hyperactivation rapidly and highly in the uncapacitated spermatozoa in vitro . These results have established a current theory that the most important initiator of hyperactivation is a rapid increase of cytoplasmic Ca 2+ that is induced by the influx from extracellular space and recruitment from the internal store …”
Section: Regulatory Mechanisms For Flagellar Hyperactivationmentioning
confidence: 74%
“…This suggests existence of strong suppressors (eg a calyculin‐sensitive protein phosphatase) for hyperactivation in the spermatozoa from livestock . Instead, hyperactivation can be induced highly in the uncapacitated spermatozoa in vitro by the treatment with the elevators of the intracellular Ca 2+ level [eg A23187 (extracellular Ca 2+ ‐dependent hyperactivation) and thimerosal (extracellular Ca 2+ ‐independent hyperactivation)], although the activation of the intracellular cAMP‐PKA signaling cascades is perhaps skipped in these spermatozoa . In our laboratory, extracellular Ca 2+ ‐dependent hyperactivation can be induced highly in bull and boar ejaculated spermatozoa by the treatment with the cell‐permeable cAMP analog to stimulate the intracellular cAMP‐PKA signaling cascades.…”
Section: Roles and Characteristics Of Flagellar Hyperactivationmentioning
confidence: 92%
See 3 more Smart Citations